2014
DOI: 10.1152/ajpgi.00085.2013
|View full text |Cite
|
Sign up to set email alerts
|

Acute ethanol preexposure promotes liver regeneration after partial hepatectomy in mice by activating ALDH2

Abstract: It is known that chronic ethanol significantly impairs liver regeneration. However, the effect of acute ethanol exposure on liver regeneration remains largely unknown. To address this question, C57Bl6/J mice were exposed to acute ethanol (6 g/kg intragastrically) for 3 days, and partial hepatectomy (PHx) was performed 24 h after the last dose. Surprisingly, acute ethanol preexposure promoted liver regeneration. This effect of ethanol did not correlate with changes in expression of cell cycle regulatory genes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 45 publications
(42 reference statements)
3
28
0
1
Order By: Relevance
“…In postmortem brain of alcohol-related disorders, elevated expression levels of ALDH2 were observed in the prefrontal cortex (Zhang et al 2014). In addition, the activity of ALDH2 in the liver was significantly increased by acute ethanol exposure (6 g/kg intragastrically for 3 days) in mice (Ding et al 2014). These results have suggested that ALDH2 gene modulation is likely presenting a compensatory regulation for ethanol metabolism, which is a potential therapeutic target for the prevention and treatment of alcohol-related disorders.…”
Section: Discussionmentioning
confidence: 98%
“…In postmortem brain of alcohol-related disorders, elevated expression levels of ALDH2 were observed in the prefrontal cortex (Zhang et al 2014). In addition, the activity of ALDH2 in the liver was significantly increased by acute ethanol exposure (6 g/kg intragastrically for 3 days) in mice (Ding et al 2014). These results have suggested that ALDH2 gene modulation is likely presenting a compensatory regulation for ethanol metabolism, which is a potential therapeutic target for the prevention and treatment of alcohol-related disorders.…”
Section: Discussionmentioning
confidence: 98%
“…Portal blood is much richer in dissolved nutrients such as glucose than arterial blood. A lack of nutrients from portal blood could alter the proliferative response [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent animal studies showed that blood lipid level was related to the ALDH2 genotype (Dunner et al 2013;Ding et al 2014;Fan et al 2014;Long et al 2013). The study in mice showed that low-to-moderate alcohol consumption increases HDL-C levels in wild-type mice but not in ALHD2-knockout mice (Fan et al 2014).…”
Section: Discussionmentioning
confidence: 99%